Semiotic Analysis of Batik in Riau Islands - Kiki Devita Sari; Aulia Putri; Nailul Himmi Hasibuan (Departement of Mathematics Education, 2023)
Batik is one of the many Indonesian cultural heritages worldwide and has become a hallmark of Indonesian society. Every Batik contains meaning. Meaning in signs is also called semiotics. This article aims to clarify the semiotic meaning of the colors and motives of the Riau Islands Batik. The researcher took the data from the interpretation of the Riau Islands' cultural symbols by the locals. In clarifying the data, the researcher was done by using qualitative methods. The result showed the semiotic meaning of Batik and how the interpretation of the Riau Islands recognized the cultural values of Batik. For practical purposes, the research results are expected to promote the culture of the Riau Islands and its characteristics for Indonesia and the international community. It is also hoped to provide knowledge about the ornaments of Riau Island to the community, especially the people of the Riau Islands, so that the cultural heritage is not lost. The data were analyzed by using Charles Sanders Pierce.